Faktor-faktor yang Mempengaruhi Turnover Intention Karyawan di PT Colamas Indah Sejati - Rahman Rahman; Wasiman Wasiman (Universitas Batanghari, 2023)
Turnover intention is the tendency or intention of employees to stop working from their jobs.